Diagnosis of hypothyroidism depending upon signs and symptoms design scoring system - Al-seidi, Fadel Abass (University of Thi-Qar Journal of Science, 2014)
Hypothyroidism may occur as a result of primary gland failure or insufficient thyroid gland stimulation by the hypothalamus or pituitary gland. It also occur when using radio-iodine. Study extended for about 2012-2013, in Thi-qar city hospital and private clinic in Republic of Iraq. 40 patients (31 women and 9 men) of suspected hypothyroidisms considered in the study. 38 patients were diagnosed as hypothyroidisms after laboratory testing of patients with thyroid function tests (TSH and T4). All of them are a positive results while the other 2 patients got negative results to TFT. According to this results we design the scoring system depending on signs and symptoms that we find in the patients. concord between above results and our system, patients get more than 12 points diagnosis as hypothyroidism, and who get less than 12 point consider non hypothyroid.